RUMOURS AND REALITIES OF MARRIAGE PRACTICES IN CONTEMPORARY SAM IN SOCIETY - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
Since the mid 19th century the Saminpeople have made a contribution to resisting the Dutch colonialrule in ruralJavathrough their non-violence movement and passiveresistance (lijdelijkverset). History also notes that they have a unique culture and system of values which reflect their own local wisdom. However, many negative rumours have become widespread regarding this community. This article explores the marriage practices in Saminsociety and investigateshow this society gives meaning to these marriage practices. It also examines whether the practice of ' virginity tests' and 'stray marriages' exist in contemporary Saminsociety.